A Small β-Carboline Derivative “B-9-3” Modulates TGF-β Signaling Pathway Causing Tumor Regression in Vivo - Zhong, Hui; Daoud, Abdelkader; Han, Jichun; An, Xiaohong; Qiao, Caili; Duan, Lanlan; Wang, Yichuan; Chen, Zhenfeng; Zhou, Jia; Shang, Jing (Frontiers in Pharmacology, 2018)
Targeting tumor microenvironment is crucial in order to overcome the anti-cancer therapy resistance. In this study, we report the antitumor activity of a newly synthesized β-carboline derivative “B-9-3”. Here, this small molecule showed a promising antitumor activity in vivo along with an enhanced immune response as reflected by a reduction of regulatory T cells and increased CD4+/CD8+ T cells. Further, B-9-3 decreased the number of myofibroblasts not only in the tumor but also in the lung suggesting an anti-metastatic action. The reduction of myofibroblasts was associated with lower expression of EMT (epithelial-to-mesenchymal transition) markers and a decrease of phosphorylated SMAD2/3 complex indicating the implication of TGF-β signaling pathway in B-9-3’s effect. The blockade of myofibroblasts induction by B-9-3 was also verified in vitro in human fibroblasts treated with TGF-β. To elucidate the mechanism of B-9-3’s action on TGF-β pathway, first, we investigated the molecular interaction between B-9-3 and TGF-β receptors using docking method. Data showed a weak interaction of B-9-3 with the ATP-binding pocket of TGFβRI but a strong one with a ternary complex formed of extracellular domains of TGFβRI, TGFβRII and TGF-β. In addition, the role of TGFβRI and TGFβRII in B-9-3’s activity was explored in vitro. B-9-3 did not decrease any of the two receptors’ protein level and only reduced phosphorylated SMAD2/3 suggesting that its effect was more probably due to its interaction with the ternary complex rather than decreasing the expression of TGF-β receptors or interfering with their ATP-binding domains. B-9-3 is a small active molecule which acts on the TGF-β signaling pathway and improves the tumor microenvironment to inhibit the proliferation and the metastasis of the tumor with the potential for clinical application.